On with critique! The necessity of critique in addressing the political deficits of responsible innovation - Lisann Penttilä (Journal of Responsible Innovation, 2024)
This article responds to the calls to address the political deficits of RI frameworks and uptakes by taking recourse to approaches inspired by the methods and emancipatory ambitions of critical theory. By outlining the results of three existing studies, important and varying dimension of R(R)I’s political deficits are identified. Despite each study identifying different aspects of the political deficit, they all share a concern for the power relations implicit in RI frameworks and uptakes. Yet, what is lacking in the critical literature is an appreciation of the role of social norms, social relations, and social structures, which is vital to an analysis and criticism of power. This article encourages RI frameworks to engage with critical practices by addressing the role these factors play in creating, exercising, and perpetuating hegemonic forms of power with the aim of greater social emancipation.